Protective effect of oxytocin on vincristine-induced gastrointestinal dysmotility in mice - Li, Shuang; Shi, Yao; Zhu, Jianchun; Li, Jingxin; Wang, Shuanglian; Liu, Chuanyong (Frontiers in Pharmacology, 2024)
Aims: Vincristine (VCR), an antineoplastic drug, induces peripheral neuropathy characterized by nerve damage limiting its use and reducing patient quality of life. VCR causes myenteric neuron damage, inhibits gastrointestinal motility, and results in constipation or paralytic ileus in patients. Oxytocin (OT) is an endogenous neuropeptide produced by enteric nerve system, regulates gastrointestinal motility and exerts neuroprotective effects. This study aimed to investigate whether OT can improve VCR-induced gastrointestinal dysmotility and evaluate the underlying mechanism. Methods: Mice were injected either with saline or VCR (0.1 mg/kg/d, i.p.) for 14 d, and OT (0.1 mg/kg/d, i.p.) was applied 1 h before each VCR injection. Gastrointestinal transit and contractile activity of isolated colonic segments was assessed. The concentration of OT in plasma was measured using ELISA. Immunofluorescence staining was performed to analyze myenteric neurons and reactive oxygen species (ROS) levels. Furthermore, the indicators of oxidative stress were detected. The protein expressions of Nrf2, ERK1/2, P-ERK1/2, p38 and P-p38 in colon were tested using western blot. Results: VCR reduced gastrointestinal transit and the responses of isolated colonic segments to electrical field stimulation, decreased the amounts of neurons. Furthermore, VCR reduced neuronal nitric oxide synthase and choline acetyltransferase immunopositive neurons in colonic myenteric nerve plexus. VCR increased the concentration of OT in plasma. Exogenous OT pretreatment ameliorated the inhibition of gastrointestinal motility and the injury of myenteric neurons caused by VCR. OT pretreatment also prevented the decrease of superoxide dismutase activity, glutathione content, total antioxidative capacity, and Nrf2 expression, the increase of ROS levels and the phosphorylation of ERK1/2 and p38 MAPK following VCR treatment. Conclusions: Our results suggest that OT pretreatment can protect enteric neurons from VCR-induced injury by inhibiting oxidative stress and MAPK pathways (ERK1/2, p38). This may be the underlying mechanism by which it alleviates gastrointestinal dysmotility.